Counter-Punishment, Communication, and Cooperation among Partners - Andrighetto, Giulia; Brandts, Jordi; Conte, Rosaria; Sabater-Mir, Jordi; Solaz, Hector; Székely, Áron; Villatoro, Daniel (Frontiers in Behavioral Neuroscience, 2016)
We study how communication affects cooperation in an experimental public goods environment with punishment and counter-punishment opportunities. Participants interacted over 30 rounds in fixed groups with fixed identifiers that allowed them to trace other group members' behavior over time. The two dimensions of communication we study are asking for a specific contribution level and having to express oneself when choosing to counter-punish. We conduct four experimental treatments, all involving a contribution stage, a punishment stage, and a counter-punishment stage in each round. In the first treatment communication is not possible at any of the stages. The second treatment allows participants to ask for a contribution level at the punishment stage and in the third treatment participants are required to send a message if they decide to counter-punish. The fourth combines the two communication channels of the second and third treatments. We find that the three treatments involving communication at any of the two relevant stages lead to significantly higher contributions than the baseline treatment. We find no difference between the three treatments with communication. We also relate our results to previous results from treatments without counter-punishment opportunities and do not find that the presence of counter-punishment leads to lower cooperation level. The overall pattern of results shows that given fixed identifiers the key factor is the presence of communication. Whenever communication is possible contributions and earnings are higher than when it is not, regardless of counter-punishment opportunities.